2012
DOI: 10.1097/ccm.0b013e3182387a6b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of real-time electronic alerting of acute kidney injury on therapeutic intervention and progression of RIFLE class*

Abstract: The real-time alerting of every worsening RIFLE class by the acute kidney injury sniffer increased the number and timeliness of early therapeutic interventions. The borderline significant improvement of short-term renal outcome in the RIFLE class risk patients needs to be confirmed in a large multicenter trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
169
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(172 citation statements)
references
References 19 publications
3
169
0
Order By: Relevance
“…Opportunities for improvement in patient care exist with identification and management of low-and high-risk AKI patients. Automated clinical surveillance systems are effective for a variety of clinical conditions including the identification of sepsis (19), adverse drug reactions (20,21), and more recently, AKI (22,23). These surveillance systems have assisted with faster identification of events compared with usual care that has been shown to improve shortterm progression of AKI severity (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opportunities for improvement in patient care exist with identification and management of low-and high-risk AKI patients. Automated clinical surveillance systems are effective for a variety of clinical conditions including the identification of sepsis (19), adverse drug reactions (20,21), and more recently, AKI (22,23). These surveillance systems have assisted with faster identification of events compared with usual care that has been shown to improve shortterm progression of AKI severity (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Automated clinical surveillance systems are effective for a variety of clinical conditions including the identification of sepsis (19), adverse drug reactions (20,21), and more recently, AKI (22,23). These surveillance systems have assisted with faster identification of events compared with usual care that has been shown to improve shortterm progression of AKI severity (22,24,25). Future studies are needed to determine the effect of clinical surveillance systems used to detect AKI on long-term recovery of renal function, as well as how these systems can be further refined to enhance the detection and management of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that the incidence of AKI can be reduced by measures, including isotonic intravenous fluid infusion before iodinated contrast administration, 28 off-versus on-pump coronary artery bypass surgery, 29 and potentially, real-time detection of incipient acute worsening of renal function 30 as well as early inpatient nephrology consultation. 31 If the AKI-BP elevation association is causal, then reducing the risk of AKI may not only reduce mortality and morbidity in the short term but also, confer large long-term public health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Our study used MAKE30, a patient-centered outcome recommended for phase III trials by the National Institute of Diabetes and Digestive and Kidney Diseases workgroup on Clinical Trials in AKI (18,20,34). Finally, although previous studies have examined informatics-based interventions (35)(36)(37) or leveraged the EHR to facilitate aspects of trial conduct (37)(38)(39), to our knowledge, this is the first large, critical care clinical trial to be conducted entirely within the EHR. By successfully enrolling nearly 1,000 critically ill adults, accurately delivering the assigned intervention in a time-sensitive manner, and collecting detailed data on patient characteristics, fluid receipt, laboratory values, and clinical outcomes, SALT demonstrated that the EHR-embedded clinical trial (13,14,40) is a powerful new tool for generating evidence to guide clinical practice in critical care.…”
Section: Original Articlementioning
confidence: 99%